Hi I know that if

ax^2 + bx + c = dx^2 + ex + f

then a=d, b=e and c=f

but how do we know this?

Of course it seems intuative but does it need to be proved?

Thanks!

Printable View

- Dec 6th 2012, 11:57 AMkinhew93General question about comparing coefficients
Hi I know that if

ax^2 + bx + c = dx^2 + ex + f

then a=d, b=e and c=f

but how do we know this?

Of course it seems intuative but does it need to be proved?

Thanks! - Dec 6th 2012, 12:38 PMLinkRe: General question about comparing coefficients
this is only true if ax² + bx + c = dx² + ex + f

**for all x**(or in fact just for some values, see why below)

Replacing x by 0 you find that c=f. So ax²+bx=dx²+e.

Now replacing x by 1 we have a+b=d+e. X by -1 we have a-b=d-e. Adding those 2 equations we have 2a=2d so a=d. Substract them so b=e.